Adsorbent for removing ions from liquid stream and method of making same

By synthesizing titanium sulfate or titanium sulfate using a titanium source containing sulfuric acid, combined with calcium hydroxide neutralization reaction, a titanium silicate medium that efficiently removes lead and mercury is solved, and the limited capacity in the prior art is achieved. Highly efficient and low-cost heavy metal removal effect.

CN119173336APending Publication Date: 2024-12-20GRAVER TECH LLC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380038404.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-03
Filing Date
2023-05-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing adsorption media have limited capacity in removing heavy metals from water, which is difficult to meet the demand for efficient removal of lead and mercury, and is costly, and the prior art has failed to effectively define the maximum capacity of the media.

Method used

By synthesizing titanium sulfate or titanium sulfate using a titanium source containing sulfuric acid, combined with calcium hydroxide neutralization reaction, adjusting the pH value and pore volume, a titanium silicate medium that efficiently removes lead and mercury, can be prepared. The titanium source can come from titanium iron titanium The precursor during ore dissolution increases the capacity and removal capacity of the medium.

Benefits of technology

Significantly improves the removal capacity of lead and mercury, improves removal efficiency by at least 10%, provides lower cost filter media, and adjusts lead and mercury capacity, achieving higher kinetic rates and greater capacity, suitable for for home and industrial water filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173336A_ABST
    Figure CN119173336A_ABST
Patent Text Reader

Abstract

An adsorption medium having a high capacity to remove heavy metals, lead and mercury, particularly when it is synthesized from a sulfur-containing titanium source, such as black liquor or titanyl sulfate (TiOSO4). The use of sulfur provides a higher adsorption capacity of lead and / or mercury than expected. A Group 1 and / or Group 2 metal titanosilicate is employed wherein the molar ratio of titanium (Ti) to silicon (Si) is 0.5-2 and the pore volume is at least less than or equal to 0.25 cc / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel adsorbent (ion exchange or sorbent) medium capable of removing cations from liquid streams, in particular divalent heavy metal cations from water. Background Art

[0002] The use of adsorbent media, including adsorption, ion exchange, and absorption, whether inorganic or organic, is well known in the art. The technical and patent literature provides numerous examples of the synthesis, use, and combination of these materials to remove metals and other contaminants from water. Ion exchange materials exchange ions based on stoichiometry and charge. Ion exchange materials are widely used in wastewater treatment and drinking water treatment. Some adsorbent materials may be inorganic. Some are pure ion exchangers, while others perform physical or chemical adsorption.

[0003] One practical application of the above materials is in point-of-entry (POE) or point-of-use (POU) water filters in the home. For example, a water softener uses ion exchange to separate calcium ions (Ca2+) and magnesium ions (Mg 2+ ) are replaced by two sodium ions (2Na + ). These materials have a limited capacity for hardness ions. When exchange is no longer occurring, the bed is either regenerated with concentrated salt or discarded. Conventional water softeners are often regenerated daily with salt to provide water with reduced calcium content to homes and protect appliances and equipment.

[0004] When evaluating the performance of an adsorbent, a comprehensive understanding of the environment in which it is removing unwanted contaminants is critical. Competing ions (chemical stress), pH, flow rate (kinetics) can all affect the ability of an adsorbent media to remove a specific contaminant. While it is common in the art to engineer new adsorbent material crystal structures to gain scientific knowledge, it is critical for the water treatment industry to design practical and cost-effective adsorbent media.

[0005] When evaluating the performance of an adsorbent, a comprehensive understanding of the environment in which the unwanted contaminant is removed is critical. Competing ions (chemical stress), pH, flow rate (kinetics) all affect the ability of an adsorbent media to remove a specific contaminant. While it is common practice in the art to engineer new adsorbent material crystal structures for scientific knowledge, it is critical for the water treatment industry to design practical and cost-effective adsorbent media.

[0006] Heavy metals may be present in trace amounts (high parts per trillion or low parts per billion) in many applications, and their presence in drinking water can impact human health. Many incidents of lead contamination have been reported due to simple chemical changes in water as it passes through lead pipes. For example, municipalities check water quality at wells or plants, but not in homes. When historical lead service pipes are used, lead can leach into the water, potentially causing harm to children and adults. Lead isn’t the only problem. The U.S. Environmental Protection Agency (EPA) regulates contaminants that enter our environment and those in our drinking water through the Clean Water Act and the Safe Drinking Water Act. The EPA regulates over 90 contaminants in drinking water, including lead, mercury, arsenic, and other heavy metals.

[0007] Adsorption media must be designed to remove heavy metals such as lead, mercury, cadmium and arsenic in order to provide safe drinking water for households.

[0008] U.S. Patent No. 5,053,139 discloses that certain amorphous titanium and tin silicate gels are capable of rapidly adsorbing various heavy metals (such as lead, cadmium, zinc, chromium, and mercury). This prior art demonstrates that titanosilicates can rapidly and efficiently adsorb heavy metal ions. These inventions are typically used in carbon block applications where the capacity and kinetic rates of the media determine how long the carbon block can remove lead or mercury from a water source. Due to the combination of ion selectivity, this invention is well suited for point-of-entry and point-of-use applications. Although this invention teaches a process for removing heavy metals, the prior art does not teach or define the maximum capacity of the media. In fact, amorphous materials are difficult to characterize because their atoms are not arranged in a periodic pattern like crystals.

[0009] Titanium dioxide has multiple crystal structures, including anatase (ubiquitous) and the less common brookite. Although the chemistry is stoichiometrically identical, the brookite form of TiO2 has a higher arsenic removal capacity. Chemical composition and structure can significantly change properties. Applying this concept to prior art titanosilicates, changes in the process of making titanosilicates can result in different chemistries and properties. The manufacturing process for these materials can be altered to optimize kinetics and capacity. Because titanosilicates are amorphous, it is more difficult to characterize these structures, so other methods are needed to identify the chemical composition. Other prior art techniques describe this by identifying the pore volume, but identifying the pore volume alone may not be related to the capacity for contaminants.

[0010] U.S. Patent Nos. 10,286,390, 9,764,315 and 9,744,518 disclose that certain amorphous titanosilicates having a pore volume of at least 0.3 cc / g (mL / g) can be used to remove heavy metals including strontium, lead, and mercury using pore forming conditions. This prior art teaches the formation of pores, wherein the pores remain at least 0.3 cc / g in all cases. However, the above patents limit the heavy metal removal performance to media having a desorption pore volume greater than or equal to 0.3 cc / g. In addition, this prior art does not define a specific total capacity for heavy metals.

[0011] The prior art clearly shows that a wide range of titanosilicates can be prepared having different properties.

[0012] All adsorption media have a finite capacity for contaminants. These are usually referred to as the pores, surfaces, or sites that the contaminant may occupy for exchange with another ion. Both monolayer and multilayer adsorption can occur, but the capacity is considered to be finite. Since a medium or mixture of media has a finite capacity, the medium or chemical can be described in terms of total capacity. Various forms of capacity are used in the literature, but are generally a function of structure and environment. Theoretical capacity is calculated, while total capacity and in-process capacity are measured. Modifications can be made to create new media with higher capacity. This is also true for titanosilicates.

[0013] Refrigerator designers need to allow for more space in their refrigerator units; consumers always want more room to store food and beverages. Water filters (for ice or drinking water) can take up a considerable amount of space. The industry needs new media with faster kinetics and higher capacity to reduce the space occupied by refrigerator block filters in a smaller volume. Titanosilicate media are used in many of these applications. If the capacity of titanosilicates could be increased, carbon block manufacturers have several options: make smaller blocks, certify blocks for larger volumes, or add new additives to the blocks to increase removal. Therefore, the introduction of new media with additional capacity is critical and important. Summary of the invention

[0014] In view of the problems and deficiencies of the prior art, one embodiment of the present invention is to provide an adsorption medium with high heavy metal removal capacity, especially lead and mercury. Studies have found that when the adsorption medium is synthesized from a titanium source containing sulfuric acid (black liquor, titanium oxysulfate (TiOSO4) or sulfur), its lead removal capacity is improved by at least 10%.

[0015] Another embodiment is to provide a filter media capable of removing heavy metals that are affected by pH.

[0016] Another embodiment is to provide a lower cost filter media that performs at least as well as the prior art in removing heavy metals, including lead and mercury.

[0017] In another embodiment, a filter media with adjustable lead and mercury capacity is provided that can be tailored to specific project needs.

[0018] In another embodiment, calcium hydroxide (slurry) is used to neutralize the reaction.

[0019] In another embodiment, the titanium source need not be pure titanyl sulfate (TiOSO4), but rather a precursor from the ilmenite dissolution process, such as titanium-iron (Ti-Fe) sulfate (TiOSO4, Ti(SO4)2, FeSO4, etc.).

[0020] Precipitation is a recommended and advantageous step in making various embodiments of the present invention. In some cases, the pH of the solution can be adjusted by adding high pH inorganic additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The features of the invention which are believed to be novel and the elements which characterize the invention are described in detail in the appended claims. The drawings are for illustrative purposes only and are not drawn to scale. However, the invention itself, both as to its organization and method of operation, may best be understood by referring to the following detailed description and the accompanying drawings:

[0022] Figure 1 is the production chemical formula of the product of the present invention;

[0023] Figure 2 is a list of theoretical and measured lead capacities of titanium-based compounds;

[0024] Figure 3 It is about the lead capacity comparison of several embodiments;

[0025] Figure 4 It is about the mercury capacity comparison of several embodiments;

[0026] Figure 5 is a graph of salt percentage versus lead (Pb) capacity (mg Pb / dry gram medium);

[0027] Figure 6 The changes in medium capacity based on different titanium solutions are shown;

[0028] Figure 7 A schematic diagram of a process for precipitating an embodiment of the present invention is depicted. DETAILED DESCRIPTION

[0029] In describing the embodiments of the present invention, reference will be made herein to Figures 1 to 7The drawings in which like numerals represent like features of the invention.

[0030] Certain terms used herein are for convenience only and do not constitute a limitation of the invention. For clarity, the same reference numbers may be used in the drawings to identify similar elements. In addition, in this specification, words such as "exemplary" and "illustrative" are used to indicate examples, instances, or illustrations. Any aspect or design described herein as "exemplary" or "illustrative" does not necessarily mean that it is more preferred or advantageous than other aspects or designs. On the contrary, the use of the word "exemplary" or "illustrative" is intended only to present the concept in a concrete way.

[0031] Figure 1 Contains possible chemical reactions (unbalanced) for producing the present invention. Soluble titanium atoms react with a mixture of hydroxide (Group 1 or Group 2) and sodium silicate to produce sodium titanium silicate and Group 1 and / or Group 2 sulfates. The stoichiometry of the final sodium titanium silicate can vary depending on the ratio of the combined elements. Metal sulfates are produced as byproducts, along with water. By filtering and washing the product, some sulfates can be removed, while others may not be washed away. Variations in water volume and methods can produce final product mixtures with different salt concentrations. The final mixing medium can have different lead capacity ranges. In all cases, the final product can be contacted with a cationic metal to obtain an ion exchange product. In certain embodiments, the counter ion of the sodium titanium silicate is not always sodium, but can be exchanged by Group 1 and / or Group 2 metals from hydroxides or other bases.

[0032] During the previous synthesis process, the pH was usually maintained at around 7. However, by synthesizing the media at a higher pH, the media itself can also have a higher pH. Lead in the water will transform from divalent lead to monovalent or particulate lead depending on the counterions and pH. When the media is synthesized at a higher pH, it is able to create local alkaline areas without affecting the pH of the water passing through the bulk. It has been determined that Pb is affected by the locally higher pH and is trapped in the pores of the media by precipitation.

[0033] The process of converting the mineral ilmenite to TiO2 involves dissolving the ilmenite (FeTiO3) in either sulfuric acid (sulfuric acid process) or chlorine gas (chlorination process). Recently, the latter process has become more popular as it is more environmentally friendly and sustainable. The unexpected result was achieved when titanium silicate synthesized using the sulfuric acid route (whether Fe is present or not) showed a higher Pb capacity. This is likely due to the hard-soft acid-base theory, as the presence of sulfuric acid or sulfur in the structure can lead to a higher Pb capacity. In inorganic chemistry, it has been shown that soft acids react more easily with soft bases than hard bases in the hard-soft acid-base theory. Importantly, this is not an application of "opposites attract". In chemistry, lead and mercury (and most heavy metals) are considered soft. Oxygen is considered hard, while sulfur is considered soft. This theory is supported by evidence in minerals found around the world. In the environment, mercury sulfide (cinnabar) and lead sulfide (sphalerite) are seen as minerals. Mercury and lead can react with the ubiquitous oxygen in the environment, but these minerals exist as stable sulfides. Other minerals containing hard metals (such as aluminum, silicon) are almost always found as oxides. It is hypothesized that when titanium silicate is synthesized in the presence of sulfur, sulfuric acid or sulfates, some of the sulfur may remain as part of the product and react more strongly with heavy metals than titanium silicate produced by the chloride process. At least one embodiment of the present invention utilizes the hard and soft acid-base theory with a higher capacity than other competing products.

[0034] like Figure 1 As shown, counterion salts are formed as a result during the manufacture of the media. Titanium silicate is precipitated by a strong base and the pH is adjusted to between 7.5 and 10. If sodium hydroxide is used, the reaction results in the precipitation of highly soluble sodium sulfate.

[0035] Calcium hydroxide (suspension) can be used for the neutralization reaction. The by-product of this reaction is slightly soluble calcium sulfate. Sulfates of Group 1 (such as Na, K, Rb, etc.) and Group 2 (such as Mg, Ca, Sr) react with ionic lead to form insoluble lead sulfate. When used as part of the final product, the lead ions will contact the filter medium of the present invention (usually a mixture of titanosilicate and active salts) and directly precipitate the lead. The actual capacity of the medium can be adjusted by washing the filter medium to control the salt content. The neutralization reaction will produce calcium sulfate. Due to the low solubility of calcium sulfate, it will remain even after washing. When water containing lead passes through, insoluble lead sulfate will be formed and calcium ions will be released. It is worth noting that this mechanism is also applicable to other metals that form strong bonds with sulfate ions, such as heavy metals.

[0036] Furthermore, the titanium source does not necessarily have to be pure titanyl sulfate (TiOSO4); rather, it can come from precursors such as titanium iron sulfides (TiOSO4, Ti(SO4)2, FeSO4, etc.) from the dissolution process of ilmenite. The complete characterization of this "black liquor" depends on the ore and the digestion process. However, this black liquor can serve as an effective source of titanium ions for sodium titanosilicate media. As the pH increases, several gel phases are observed. The iron titanosilicate product undergoes several gel phases, but the final product is expected to be either sodium-titanium-iron silicate or sodium-titanium silicate iron oxide. Iron oxides and sulfates are known in the art to remove oxyanions, depending on the pH. Surprisingly, the addition of iron to the mixture does not reduce the capacity for lead or mercury. The addition of these elements from ilmenite may result in additional unexpected properties, such as anion exchange functionality. For example, hexavalent chromium is an industrial byproduct that may enter drinking water sources. There is a pressing need to remove hexavalent chromium (as chromate) from drinking water sources. Iron is introduced into the present invention to increase the ability to remove oxyanions. Basically, this embodiment combines a coprecipitation route to formulate a new media. Even with the presence of iron, the capacity of the media for Pb and Hg is the same as in the absence of Fe.

[0037] Recent synthetic innovations may lead to different processes to achieve this invention. Advances in mechanochemistry, hydrothermal chemistry, or other synthetic processes could conceivably be used to make this product. Titanium dioxide can be converted to titanates in a hydrothermal synthesis. Likewise, titanosilicates can be prepared by the same process. Other embodiments of the invention are envisioned in the presence of sulfuric acid, sulfur, or sulfuric acid. Similarly, mechanochemistry (providing the synthesis energy by mechanical means) could be used to convert titanium dioxide or other forms of titanium.

[0038] In an embodiment of the present invention, a medium for removing metal cations is introduced, wherein the medium includes a Group 1 and / or Group 2 metal titanosilicate. The medium is limited to a molar ratio of titanium (Ti) to silicon (Si) of 0.5-2 and a pore volume less than or equal to 0.25cc / g. The medium performance shows a lead capacity of at least 280mg / dry g at a lead concentration of 500ppm, or a mercury capacity of at least 25mg Hg / dry g at a mercury concentration of 50ppm. In at least one embodiment, the Group 1 metal is sodium and / or the Group 2 metal is calcium. The medium may further include Group 1 and / or Group 2 salts that may be adjusted to optimize the removal of heavy metals. The medium may be synthesized from black liquor or titanyl sulfate (TiOSO4).

[0039] Typically, a sulfur reactant is used in the synthesis process, wherein the sulfur reactant is contained in a titanium source. The titanium source is a precursor from a ferro-titanium ore dissolution process, including titanium-iron (Ti-Fe) sulfate or ferrous sulfate. Titanium-iron (Ti-Fe) sulfates include titanyl sulfate (TiOSO4) or titanium sulfate (Ti(SO4)2). Titanosilicates in metal titanosilicates can be synthesized from titanium products in sulfuric acid. The mediator may include sulfates or oxides of iron or manganese or other byproducts from a ferro-titanium ore dissolution process.

[0040] In at least one embodiment, the media is synthesized from a titanium source containing sulfuric acid. Such synthesis may utilize black liquor or titanyl sulfate (TiOSO4). Additionally, titanosilicates may be synthesized from titanium production in sulfuric acid.

[0041] Figure 2 Assumed titanium-based stoichiometries are listed. Theoretical capacities for lead are calculated. Unrealized changes such as lattice distortion, vacancies, dislocations, dopants, and substitutions may improve or deteriorate these capacities. In all cases, the embodiments of the present invention have a total lead capacity of over 280 mg / g. It has been demonstrated that the capacity of the prior art is less than 280 mg / g, indicating that the measurable capacity is not directly related to the theoretical capacity or stoichiometry. This also shows that the embodiments of the present invention have measurably greater capacity and are independent of stoichiometry.

[0042] Figure 3 Several examples of the present invention are shown in comparison with competing materials on the market in terms of their electrical conductivity. Examples AC represent different variations of the present invention and different manufacturing processes. All examples were synthesized using a titanium sulfate solution, but with different levels of soluble salts. Example A contained 1% soluble salts, Example B contained 4.8% soluble salts, and Example C contained 15.1% soluble salts. The results show that the capacity of each example can vary. For example, Example A has a capacity of 305.2 mg Pb / drg g of media. This is an unexpected result because the capacity of conventional filter media is expected to be the same as Material 2 in U.S. Patent No. 5,053,139, which according to the studies presented has a lower capacity of 259.5 mg Pb per dry gram of media.

[0043] Figure 4 A comparison of several examples of the invention in terms of mercury capacity is presented. Examples A and B maintain at least the same capacity as the prior art, while showing significantly improved lead capacity.

[0044] Figure 5is an example showing how the salt content of the product changes. This can be achieved by varying wash levels or by changing the basis used to precipitate the example. From 0% salt to approximately 16% salt, the capacity increases significantly, from 300 mg / g to approximately 500 mg / g. However, beyond 18% salt, the trend is limited and levels off.

[0045] Figure 6 The variation in media capacity based on different titanium solutions is shown. Using "black liquor" for 100% reaction results in the highest lead and mercury capacity. In contrast, Example D was synthesized using black liquor. Example E was synthesized using a titanyl sulfate (TiOSO4) solution.

[0046] Figure 7 A schematic diagram of a process for precipitating an embodiment of the present invention is depicted. This process is performed at a lower pH (7.5). Solution (B) contains 214 gallons of water, 25% sodium hydroxide, and sodium silicate. This solution is then mixed with 144 gallons of water and 59 gallons of titanyl sulfate solution, and 32 gallons of sodium hydroxide (NaOH) are added. Please note that the volume numbers are calculated based on a titanium (Ti) to silicon (Si) ratio of 1:1 (molar). Other embodiments adjust the titanium (Ti) to silicon (Si) ratio between 0.5 and 2.0, depending on the desired results. The resulting pore volume is between 0.02–0.07cc / g, and experiments have shown that its lead capacity is higher than the baseline media.

[0047] In the first process, titanium sulfate produced by the sulfuric acid process is added to deionized water and placed in container A. Water glass is added to 50% sodium hydroxide and deionized water and placed in container B. The amount of chemical added is such that the molar ratio of titanium (Ti) to silicon (Si) is about 1:1. The ratio of sodium hydroxide to water can be adjusted to achieve the desired target (such as pH, solid content in the slurry, etc.). The contents of the two containers are then stirred. The alkaline mixture in container B is slowly added to container A over a period of 30 minutes to 95 minutes. The pH is then measured to be about 1.58. The pH is then adjusted with 50% NaOH to a standard unit between 8.0 and 9.05. After the sample is mixed for 10 minutes, the agitator is turned off and the solution is allowed to stand for 1 hour. The pH is rechecked to ensure that it is between 8.5 and 9.5. The solution is then filtered and washed with water until the conductivity drops to 2500MS (2500μS / cm). The resulting filtered product is dried. If necessary, the filtrate can be formed into a cake. The resulting cake can be reslurried by spray drying and dried. After drying of the resulting filtered product, the pore volume of the media was measured to be less than 0.3 cc / g.

[0048] In another process embodiment, the titanium source comes from a solution / suspension containing dissolved ilmenite liquid (black liquor). The titanium source may contain iron, sulfate, sulfuric acid, titanium, manganese and other impurities that may be present in the ilmenite. The liquid is diluted with water and placed in a first container. Water glass and sodium hydroxide are weighed into a second container. The ideal molar ratio of titanium to silicon is between 0.5 and 2.0. When added in this manner, the pore volume will be significantly less than 0.3cc / g. The calculated pore volume of less than 0.15cc / g is an unexpected result because intuitively a higher pore volume means more lead removal sites. However, these data show that high capacity can be achieved with small pore volumes as demonstrated in the embodiments of the present invention.

[0049] In at least one embodiment, the present invention includes a process for removing heavy metals, the process comprising contacting a solution containing heavy metals with a Group 1 and / or Group 2 metal-titanosilicate, wherein the molar ratio of titanium (Ti) to silicon (Si) is 0.5-2, the pore volume is about less than or equal to 0.25 cc / g, and has a lead capacity of at least 280 mg / dry g at a lead concentration of 500 ppm and / or a mercury capacity of at least 25 mg / g at a mercury concentration of 30 ppm.

[0050] A method for preparing an adsorbent for removing ions from a liquid stream comprises: reacting soluble titanium with a hydroxide and sodium silicate mixture to produce a product of titanosilicate and Group 1 and / or Group 2 sulfates; and filtering and washing the product to remove sodium sulfate. The process also includes combining titanyl sulfate (TiOSO4) + sulfuric acid (H2SO4) + water (H2O) with sodium silicate (Na2SiO3) + sodium hydroxide (NaOH) + water (H2O). In this process, the use of a calcium hydroxide slurry to neutralize the reaction is an option. Soluble titanium can be obtained from titanium-iron (Ti-Fe) sulfate.

[0051] When preparing the adsorbent, further considerations include, but are not limited to:

[0052] a) the product is spray dried to a size of 25-80 μm D50;

[0053] b) Adding iron or other transition metals to the process to reduce costs;

[0054] c) the reaction is carried out at room temperature; and

[0055] d) TiO2 can be dissolved at temperatures exceeding 200°C and then react with sodium silicate and sodium hydroxide to form products.

[0056] The capacity of the medium can be measured by contacting 100 mg dry weight of the medium with a solution containing approximately 500 ppm Pb2+. The lead solution is made by dissolving lead nitrate in deionized water. The pH does not need to be adjusted. The sample is placed on a shaker for 10 to 16 hours. The solution is filtered through a 0.45 μm filter and analyzed for Pb content. The capacity is calculated according to the following formula:

[0057] Q=(C0-C f )*(V / m) / 1000

[0058] in:

[0059] Q represents the number of milligrams of pollutants adsorbed per gram of dry weight of the medium;

[0060] C0 represents the concentration of pollutants in the initial solution (ppm);

[0061] C f It indicates the final concentration of the pollutant in the solution after the reaction (ppm);

[0062] V represents the volume of solution used (ml); and

[0063] m represents the mass of dry weight medium used (g).

[0064] The media is used as is, but calculations can be performed to standardize the moisture content. This process can be used to evaluate a wide variety of media.

[0065] According to one embodiment of the present invention, the adsorbent can be prepared by the following steps: a) mixing soluble titanium with hydroxide and sodium silicate to react to generate a product of titanosilicate and Group 1 and / or Group 2 sulfate; filtering and washing the product to remove sodium sulfate, wherein the titanium source comes from Ti-Fe-sulfate.

[0066] Although the present invention has been particularly described in conjunction with specific preferred embodiments, it will be apparent to those skilled in the art upon reading the above description that many alternatives, modifications and variations are possible. Therefore, the appended claims are intended to cover any such alternatives, modifications and variations as long as they fall within the true scope and spirit of the present invention.

Claims

1. A media for removing metal cations comprising a Group 1 and / or Group 2 metal titanosilicate having a titanium (Ti) to silicon (Si) molar ratio of 0.5-2, a pore volume less than or equal to 0.25 cc / g, and a lead capacity of at least 280 mg / dry g at 500 ppm Pb.

2. The medium of claim 1 having a mercury capacity of at least 25 mg Hg / dry g at 50 ppm Hg.

3. The medium according to claim 1, characterized in that The Group 1 metal is sodium.

4. The medium according to claim 1, characterized in that The Group 2 metal is calcium.

5. The medium according to claim 1, characterized in that A sulfur reactant is included for synthesis.

6. The medium according to claim 5, characterized in that The sulfur reactant is contained in the titanium source.

7. The medium according to claim 1, characterized in that The media is synthesized by using black liquor and / or titanyl sulfate (TiOSO4).

8. The medium according to claim 1, characterized in that The titanosilicate in the metal titanosilicate is synthesized by titanium production from sulfate.

9. The medium according to claim 6, characterized in that The titanium source is a precursor from the ilmenite dissolution process, including titanium-iron (Ti-Fe) sulfate or ferrous sulfate (FeSO4).

10. The medium according to claim 9, characterized in that The titanium-iron (Ti—Fe) sulfate includes titanyl sulfate (TiOSO 4 ) or titanium sulfate (Ti(SO 4 ) 2 ).

11. The medium according to claim 1, characterized in that Group 1 and / or Group 2 salts are included.

12. The medium according to claim 1, characterized in that Contains sulphates or oxides of Fe and / or Mn or other by-products from the ilmenite dissolution process.

13. The medium according to claim 11, characterized in that The Group 1 or Group 2 salt is tailored to optimize the removal of heavy metals.

14. A method for removing heavy metals comprising contacting a solution containing heavy metals with a medium comprising Group 1 and / or Group 2 metal titanosilicates having a titanium (Ti) to silicon (Si) molar ratio of 0.5-2, a pore volume less than or equal to 0.25 cc / g, and a lead capacity of at least 280 mg / dry g at 500 ppm Pb.

15. The method according to claim 14, characterized in that The media has a mercury capacity of at least 25 mg / g at 30 ppm Hg.

16. A method of producing an adsorbent for removing ions from a liquid stream, comprising: reacting soluble titanium with a hydroxide and sodium silicate mixture to produce a product of titanosilicate and Group 1 and / or Group 2 sulfate; The product is filtered and washed to remove metal sulfate.

17. The method according to claim 16, characterized in that The steps include combining titanyl sulfate (TiOSO4) + sulfuric acid (H2SO4) + water (H2O) with sodium silicate (Na2SiO3) + sodium hydroxide (NaOH) + water (H2O).

18. The method according to claim 16, characterized in that This involves using a calcium hydroxide slurry to neutralize the reaction.

19. The method according to claim 16, characterized in that The titanium is derived from titanium-iron (Ti-Fe) sulfate.

Citation Information

Cited By

  • Titanium-silicon composite resin heavy metal adsorption material and preparation method thereof

    CN122912826A